Sosialisasi Pemanfaatan Sampah Organik Menjadi Eco-enzyme Bagi Tim Penggerak PKK Rejoso, Nganjuk - Chrystia Aji Putra; Raden Balqis Ibrah Fakhira; Novia Nirmala Putri; Raihan Nur Rafi; Septian Nurul Istiqfaroh (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Rejoso, located in Nganjuk Regency, lacks adequate waste management facilities such as waste banks, composting, and landfills. Therefore, there is a pressing need to address waste management, particularly food waste. One effective method is converting organic waste, specifically leftover fruits and vegetables, into eco-enzyme. Members of the Tim Penggerak PKK can play a pivotal role in promoting organic waste management through eco-enzyme production. To facilitate this initiative, it is crucial to conduct a socialization, first and foremost, campaign on utilizing organic waste for eco-enzyme production among the Tim Penggerak PKK in Rejoso. This aims to foster sustainable and environmentally-friendly organic waste management practices. The approach involves three main activities: educating households on waste management, providing training on eco-enzyme production, and demonstrating the eco-enzyme production process.